Discussion of “Representation of People’s Decisions in Health Information Systems: A Complementary Approach for Understanding Health Care Systems and Population Health” - Al-Shorbaji, Najeeb; Borycki, Elizabeth M.; Kimura, Michio; Lehmann, Christoph U.; Lorenzi, Nancy M.; Moura, Lincoln A.; Winter, Alfred (Methods of Information in Medicine, 2017)
This article is part of a For-Discussion-Section of Methods of Information in Medicine about the paper “Representation of People’s Decisions in Health Information Systems: A Complementary Approach for Understanding Health Care Systems and Population Health” written by Fernan Gonzalez Bernaldo de Qui-ros, Adriana Ruth Dawidowski, and Silvana Figar. It is introduced by an editorial. This article contains the combined commentaries invited to independently comment on the paper of de Quiros, Dawidowski, and Figar. In subsequent issues the discussion can continue through letters to the editor.
Keywords: Population health; learning health systems; health information systems; complex systems thinking; social theory